No correlation between picky eating and nutritional status of toddlers aged 24-59 months in Denpasar City, Bali Province - Pratiwi, Rinda Dian; Sutiari, Ni Ketut; Utami, Ni Wayan Arya (Public Health and Preventive Medicine Archive, 2022)
Background and purpose: Picky eating behaviour in toddlers may lead to a lack of nutritional intake and affect their nutritional status. This study aims to determine the correlation of picky eating with the nutritional status of toddlers aged 24-59 months in Denpasar City. Methods: This is a cross-sectional study of 100 toddlers and mothers in Denpasar City in 2020. The variables collected were mother's education, occupation, family income, children’s age, gender, history of infectious diseases, eating behaviour, and nutritional status. The data were collected by interview using questionnaire for socio-demographic characteristics and the Children Eating Behaviour Questionnaire (CEBQ). Bodyweight and height were measured using Camry and Microtoise digital scales. The data were analyzed including descriptive analysis and chi-square test, Results: We found almost two third (63%) of the toddlers had picky eating behaviour. Most toddlers had normal nutritional status (87%), while 9% of them were stunted. Most toddlers had a poor appetite (85%) and left food on their plates after eating (54%). The majority do not want to taste food that was never introduced (66%) and refuse the main meal after eating snacks (68%). We found no significant association between eating behaviours and nutritional status of the toddlers. Conclusion: There was no correlation between picky eating behaviour and the nutritional status of toddlers. Picky eaters do not refuse food consistently, hence it can balance the nutritional needs. Therefore, providing information and practice regarding nutritious food is still important, as well as regular monitoring of children’s nutritional status.